Analisis Sistem Penyaliran Tambang Terbuka Penambangan Batubara di PT. Kalimantan Prima Persada Jobsite PCNS, Desa Sebamban, Kec. Sungai Loban, Kab. Tanah Bumbu, Provinsi Kalimantan Selatan - Putri Arrina Haq; Rusli Har (Departemen Teknik Pertambangan FT UNP, 2022)
PT. Kalimantan Prima Persada PCNS Jobsite is one of the coal mining companies engaged in mining contractor. Mining activities are carried out using the open pit mining method, which causes the formation of a basin that is wide enough and has the potential to become a water storage area, both from surface runoff and groundwater. Based on the results of the calculation of rainfall for a period of 12 years, from 2010-2021, with a catchment area of 216,03 Ha, the planned rainfall value is 182,38 mm in a 10-year return period, with a rainfall intensity of 62,46 mm/hour and runoff discharge of 20,2 /second. Based on observations of field conditions by looking at the difference in the initial and final elevations that occur in the Majapahit Pit sump, the amount of groundwater that enters the Majapahit Pit sump is 1,35 /second. The total water discharge which is the overall discharge that will be accommodated in the sump is 21,55 /second. For the total pump head that must be provided to drain the amount of water as planned is 106,2 m, with a pump power of 32,77 kW or 43,94 Hp, then the pumping activity with one available pump is only able to dry 20% of the total sump capacity. The volume of water in the sump in a day after pumping is 1.847.017,12 .. Recalculation of the sump dimensions at the research site is not necessary, because there is no economical coal reserve under the sump. For an economical open channel design, it is known that the bottom width of the channel (b) is 1,25 m, the hydraulic depth (y) is 1,5 m, the wet cross-sectional area is (A) 3,18 , the wet perimeter (P) is 4,71 m, the hydraulic radius (R) is 0,75 m, the length of the channel slope (a) is 1,495 m, the top surface width (B) is 2,99 m and the channel guard height (W) is 0,86 m, the open channel discharge is 4,8 /second so it can accommodate the pumping discharge issued at the outlet which is 0,216 /second. The volume of the sludge settling pond which made by the Engineering Department of PT. Kalimantan Prima Persada PCNS Jobsite is 65.289 so it can accommodate if the rainfall is high, which is 64.880,95 and there is no need to add another pond.